Linguistic indicators of negative-perspective language in women’s depressive disorder - Klaisingto, Phennapha (Humanities, Arts and Social Sciences Studies, 2021)
Depressive disorder impacts physical health and affects a patient’s life. Analyzing the language of depressive disorder patients can serve as a means of psychological assessment. This study analyzes the negative perspective of depressive disorder patients via linguistic analysis in 12 female patients from Lampang Hospital. Data was collected through interviews conducted with the patients in which they discussed their depressive experiences. Through Systemic Functional Linguistics, it is proven that linguistic analysis can be used to represent the negative perspective of patients with depression. The results show that the negative perspective of depression can be indicated on all linguistic levels: textual, syntactic, lexical, and pragmatic. At the textual level, thematic analysis and connectors are analyzed in the data. At the syntactic level, transitivity is analyzed to reflect the ideational function of patients through four processes: material, relational, mental, and existential. At the lexical level, lexical choice is analyzed to represent the negative experience of patients. The negative perspectives are indicated in various ways, such as negative thought, negative routine, negative behavior, hedging, and referencing. At the pragmatic level, conceptual metaphor, self-blame, and presupposition can represent the negative perspective of patients with depression. This research shows that linguistic strategies of analysis can indicate the language functions of a female patient with depressive disorder.